Value of Non-Invasive Markers of Coronary Artery Patency after Thrombolytic Therapy in Acute Myocardial Infarction (Faridpur Medical College Journal, 2025)
Acute myocardial infarction is a potentially life-threatening condition and patient may die or become disabled in the prime of life. This hospital based observational study was conducted in medicine and cardiology department of Faridpur Medical College Hospital from 25th March 2015 to 24th September 2015 among patients with acute myocardial infarction to see the value of non-invasive markers (ST resolution and CK-MB peaking) in the detection of reperfusion after thrombolysis. Total 100 consecutive patients with their first myocardial infarction undergoing thrombolytic therapy were included in the study.  Study shows maximum number of patients 49 (49%) were between 51-60 years’ age group, next 26 (26%) were between the age group of 61-70 years.  Total 78% were male and 22% were female & majority of the acute myocardial infarction were inferior (57%). Present study showed that 86% of patients succeed to reperfusion and 14% fail to reperfusion. Blood samples were taken on admission and 90 minutes after thrombolytic therapy. The times at which the concentrations of the CK-MB markers peaked significantly at 90 minutes in patients of reperfused group (88%) than in those of not reperfused (12%). These results emphasize the release of these markers when reperfusion is established.Faridpur Med. Coll. J. 2025;20(1): 36-40